PENGARUH UKURAN PERUSAHAAN DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Y. Djoko Suseno, Istamarwati & (Universitas Slamet Riyadi, 2017)
The purpose of this study are to: 1) analyze effect of size on profitability2) analyze effect of debt to equity ratio on probability. 3) analyze effect of sizeon firm value 4) analyze effect of debt to equity ratio on firm value 5) analyzeeffect of profitability on firm value 6) to analyze the effect of size on firm valuewith profitability as intervening variable 7) analyze the effect of debt to equityratio on firm value with profitability as intervening variable This type ofresearch is empirical research in food and beverages companies are listed inthe Indonesian Stock Exchange in 2011-2015. A sample of 15 companieswith a total sampling technique. Analysis data used path analysis. The resultsshowed the size has no significant effect on profitability. Debt to equity ratiohas significant effect on profitability. Size has a significant effect on firmvalue. Debt to equity ratio has a significant effect on firm value. Profitabilityhas significant effect on fiirm value. Profitability does not mediate the effect ofsize on firm value. Profitability are mediated the effect of debt to equity ratioon firm valueKeywords: size, debt to equity ratio, profitability, firm value